The influence of financial technology, social environment, and financial attitudes on the financial behavior of PSDKU UNTAD Morowali - Erwan Sastrawan Farid; Tiara; Munawarah; Rian Risendy; Nini Andriani (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Studi This study aims to determine the effect of financial technology, social environment, and financial attitudes on the financial behavior of UNTAD Morowali PSDKU students. The type of research used in the study is quantitative. The research method uses non probability sampling with purposive sampling technique. The data collection technique used a questionnaire. The population used in this study were UNTAD Morowali PSDKU students. The sample taken was 50 respondents. The data analysis technique used multiple linear regression with the help of SPSS version 25. The results showed that 1) based on the results of the F test, it shows that financial technology variables, social environment, and financial attitudes have a positive and significant effect on the financial behavior of PSDKU UNTAD Morowali students. 2) Financial technology variables have a positive and significant effect on the financial behavior of PSDKU UNTAD Morowali students 3) The social environment variable has a positive and insignificant coefficients value, which means that the social environment has no role in the financial behavior of PSDKU UNTAD Morowali students. 4) The financial attitude variable has a positive and insignificant coefficients value, which means that financial attitudes have no role in the financial behavior of PSDKU UNTAD Morowali students